The thirteen ghosts - Stilton, Geronimo; Bigarella, Ivan, 1984-; Campioni, Giorgio; Dami, Elisabetta (New York : Scholastic, 2011)
Creepella von Cacklefur visits Squeakspeare Mansion with her niece, Shivereen, and meet Bobby Squeakspeare, a descendent of the famous William Squeakspeare, but the mansion is filled with spooky ghosts.
"Based on an idea by Elisabetta Dami"--T.p. verso.
"Geronimo Stilton"--Cover.
Translation of: Tredici fantasmi per tenebrosa.
3.4.
3-6
edited hb 2015-06-16
Keywords: Dwellings -- Fiction; Ghost stories; Mice -- Fiction; Ghost stories